2020
DOI: 10.3390/jcm9030832
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy Assessment of Molded, Patient-Specific Polymethylmethacrylate Craniofacial Implants Compared to Their 3D Printed Originals

Abstract: The use of patient-specific implants (PSIs) in craniofacial surgery is often limited due to a lack of expertise and/or production costs. Therefore, a simple and cost-efficient template-based fabrication workflow has been developed to overcome these disadvantages. The aim of this study is to assess the accuracy of PSIs made from their original templates. For a representative cranial defect (CRD) and a temporo-orbital defect (TOD), ten PSIs were made from polymethylmethacrylate (PMMA) using computer-aided design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

4
6

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 36 publications
1
34
0
Order By: Relevance
“…In the anatomical design modeling phase, .STL file of the 3D volumetric reconstructed model (Figure 2A) was imported into a medically certified CAD modeling software (3-matic Medical v. 13.0, Materialise, Leuven, Belgium). For the precise reconstruction of the virtual cranial defect, a mirror-based reconstruction approach was followed (Benazzi and Senck, 2011;Chamo et al, 2020). First, a datum plane (mid-plane reference system) was created, and the healthy (non-defect) side was mirrored to the defect side.…”
Section: Three-dimensional (3d) Modeling and Design Process Of Patienmentioning
confidence: 99%
“…In the anatomical design modeling phase, .STL file of the 3D volumetric reconstructed model (Figure 2A) was imported into a medically certified CAD modeling software (3-matic Medical v. 13.0, Materialise, Leuven, Belgium). For the precise reconstruction of the virtual cranial defect, a mirror-based reconstruction approach was followed (Benazzi and Senck, 2011;Chamo et al, 2020). First, a datum plane (mid-plane reference system) was created, and the healthy (non-defect) side was mirrored to the defect side.…”
Section: Three-dimensional (3d) Modeling and Design Process Of Patienmentioning
confidence: 99%
“…There have been several reports on applying point-of-care (POC) 3D printing in numerous avenues, including the fabrication of anatomical biomodels for preoperative surgical planning, surgical guides, and prosthetic aids [18,19]. Particularly in the context of cranioplasty, recently published reports have demonstrated the fabrication of customized acrylic cranioplasty implants in hospitals assisted by 3D-printed molds [20][21][22][23]. However, very few reports have addressed the avenue of POC manufacturing of 3D-printed personalized implants.…”
Section: Introductionmentioning
confidence: 99%
“…The level of accuracy required in a PSI depends on the clinical application. According to our results, PSIs in Group 1 and Group 2 were within the acceptable accuracy range required in cranioplasty procedures, with overall 3D deviations under 2 mm [ 27 ]. Further analysis of the spatial distribution of variations revealed that the deviation pattern depended on the size and shape of the cranial defect, which was reflected in the PSIs fabricated ( Figure 8 ).…”
Section: Discussionmentioning
confidence: 94%